Refactoring and Rebirth of traditional residential buildings based on the reconstruction of Yi Minority Country - Gu Ruiping; Lan Shuwei; Ding Ning; Qiu Ling; Li Xiaoran (E3S Web of Conferences, 2024)
The protection and renewal of traditional residential buildings help to enhance the functionality and adaptability of the buildings, pass on the traditional architectural culture, promote the sustainable development of traditional buildings, and contribute to rural revitalization. This article proposes some practical strategies for the protection and renovation of traditional residential buildings, and elaborates in detail on the long-term development of the reconstruction and renovation of traditional Yi ethnic villages’ residential buildings in Damoyu Village, Kunming City and Dabudong Village, Luoping County. It can provide methodological references for the renovation and reuse of traditional residential buildings.